Using Games to Develop English Speaking Skills in Children - Kaushik, Ruchi (THE PRIMARY TEACHER, 2018)
Children, at the primary stage, have an innate ability to acquire and learn a new language. Therefore, it is important for teachers to provide them with a stress free environment so that learning may become fun, and the young learners may feel inclined to learn the language (i.e., the second language or L2, apart from their mother tongue or native language) in a natural way without feeling intimidated or burdened. In the Indian context, this second language is mostly English. Research studies indicate that fun activities and games make English classes enjoyable. This article reviews some research studies that describe how games and fun activities are beneficial in teaching English to students at the primary stage. It also points out that many teachers use games as warm-up activities or fillers, which may be incorporated meaningfully in prescribed lessons for developing students’ communicative skills, particularly, spoken English